Hearing Impairment Caused by Noise at the Workplace - zahirovic, Zerina; Omerbasic, Ago; Milanovic, Ermina Sitnic-; Salcin, Edina Lazovic- (American Scientific Research Journal for Engineering, Technology, and Sciences, 2021)
Objectives: The aim of this article is to determine the prevalence of hearing impairment caused by noise among workers in two companies in Bosnia and Herzegovina, to correlate hearing loss with age and years of specific work experience, and to indicate the occurrence mechanisms for these impairments. Methods: The study included 60 respondents who were divided into two groups: one group consisted of respondents with hearing impairment, and the second group respondents whose hearing was not impaired. Data were collected over a period of 5 years, by testing with sounds in frequency range 250-8000 Hz, which were graphically represented by audiograms. Statistical processing and comparison of the results of the control group and the group with hearing impairment were performed. Results: The age of the respondents ranged from 31 to 65 years, and the length of service ranged from 1 to 37 years. Hearing impairment was found in 46 workers, while the rest of the respondents had normal hearing. The average value of the hearing threshold in respondents with hearing impairment at 1 kHz was 21 dB, and the average value of hearing impairment was 34.45 dB (mild hearing impairment). Majority of workers have a mild degree of impairment. The largest differences in the audibility threshold between the two groups of workers with and without impairment were noticed at 4 kHz in the age group 46 to 55 years, and in the group with work experience from 21 to 30 years. Conclusion: Workplace noise effects are most clear in the 4 kHz frequency range. The age of the respondents and the years of work experience are significantly correlated with the hearing impairment: older workers and workers with longer work experience have greater hearing impairments.